Fear of missing out dan personal growth initiative pada mahasiswa - Putri, Nabia Febriani; Saraswati, Putri (Universitas Muhammadiyah Malang, 2023)
Abstrak. Students’ inability to adapt can cause students to become stressed and pessimistic. Students who feel stressed and pessimistic indicate that the student has poor Personal Growth Initiative (PGI) and will more easily experience Fear of Missing Out (FoMO). The purpose of this research is to see the relationship between FoMOt and PGI in students. The respondents of this research were 394 students who were studying in Indonesia. The sampling technique uses convenience sampling. This research was measured using the Fear of Missing Out Scale (FoMOS) and Personal Growth Initiative Scale-II (PGIS-II). The results of the analysis were carried out using a correlation test with a value of r=0.009; p=0.853 (p>0.05) does not show a relationship between FoMO and PGI in students. The results of this research show that high or low levels of PGI are not necessarily influenced by the level of FoMO in students. Keyword: Child of divorce, defense mechanism, psychological well-being